2020
DOI: 10.1039/d0ra05192f
|View full text |Cite|
|
Sign up to set email alerts
|

A hierarchical Ca/TiO2/NH2-MIL-125 nanocomposite photocatalyst for solar visible light induced photodegradation of organic dye pollutants in water

Abstract: In this study, for the first time, the Ca/TiO2/NH2-MIL-125 nanocomposite photocatalyst was synthesized for the purpose of photodegradation of Methyl Orange (MO) and Rhodamine B (RhB) dyes under visible light irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(16 citation statements)
references
References 58 publications
0
15
0
1
Order By: Relevance
“…FESEM images distribute the presence of spherical β-Bi 2 O 3 nanoparticles evenly on the surface of TiO 2 particles. As can be seen, the particles using this preparation method are somewhat accumulated, which this accumulates may be attributed to the evaporation of organic matter adsorbed on the nanoparticle surface and structural changes as well as the lack of sonicates of the samples before imaging [5] . It can be concluded that, under the current path, bismuth metal nanoparticles are formed by hydrothermal reaction and after the calcination is completely transformed into TiO 2 /β-Bi 2 O 3 composite nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…FESEM images distribute the presence of spherical β-Bi 2 O 3 nanoparticles evenly on the surface of TiO 2 particles. As can be seen, the particles using this preparation method are somewhat accumulated, which this accumulates may be attributed to the evaporation of organic matter adsorbed on the nanoparticle surface and structural changes as well as the lack of sonicates of the samples before imaging [5] . It can be concluded that, under the current path, bismuth metal nanoparticles are formed by hydrothermal reaction and after the calcination is completely transformed into TiO 2 /β-Bi 2 O 3 composite nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…AFM analysis is possible to determine the roughness and predicted surface parameters of TiO 2 /β-Bi 2 O 3 layers. Figure [5] shows an AFM micrograph of the surface of TiO 2 /β-Bi 2 O 3 layers. As can be seen, the surface of the TiO 2 /β-Bi 2 O 3 layers with Ra=152nm and Rq=191nm show a calculated surface area of 1.318 μm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Over pH 6.2, the photodegradation efficiency decreases due to a lower density of the hydroxyl radicals, thus a less oxidation potential [ 46 ]. Another reason for the lower photodegradation efficiency under alkaline conditions is the formation of insoluble compounds in the media, which hampers light penetration and thereby leads to a reduction in generation of the hydroxyl radicals [ 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%